2017
DOI: 10.1002/admi.201700559
|View full text |Cite
|
Sign up to set email alerts
|

Negligible Electronic Contribution to Heat Transfer across Intrinsic Metal/Graphene Interfaces

Abstract: Despite the importance of high thermal conductance (i.e., low thermal resistance) of metal contacts to thermal management of graphene devices, prior reported thermal conductance (G) of metal/graphene interfaces are all relatively low, only 20-40 MW m -2 K -1 . One possible route to improve the thermal conductance of metal/graphene interfaces is through additional heat conduction by electrons, since graphene can be easily doped by metals. In this paper, we evaluate the electronic heat conduction across metal/gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 54 publications
(110 reference statements)
2
52
0
Order By: Relevance
“…Finally, the TBC predicted using α 12,fit is shown in Figure along with TBC for Ti/G, Ti/h‐BN, and h‐BN/G from our TDTR results. Various literature results for h‐BN/G, metal/G, and metal/graphite interfaces are also shown for comparison. The discrepancy between h‐BN/G results for the A‐DMM and PWA‐DMM models at low temperatures arises from the assumption of constant α 12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the TBC predicted using α 12,fit is shown in Figure along with TBC for Ti/G, Ti/h‐BN, and h‐BN/G from our TDTR results. Various literature results for h‐BN/G, metal/G, and metal/graphite interfaces are also shown for comparison. The discrepancy between h‐BN/G results for the A‐DMM and PWA‐DMM models at low temperatures arises from the assumption of constant α 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Also shown are previously reported values of h‐BN/G TBC from studies by Chen et al (open left purple triangle), Liu et al (open purple diamond), and Kim et al (open purple trapezoid) using Raman spectroscopy. For further comparison, TBC for various metal/G [Al/O‐G (open black square), Pd/G (open up black triangle), and Ag/G (open right black triangle) and Ti/graphite (open gray circles) interfaces are also shown.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the low thermal conductance across the basal planes could limit the performance of the nanodevices of layered materials. For example, heat dissipation from hot spots in graphene-based nanodevices is limited by the poor thermal conductance of graphene interfaces, [15][16][17][18] despite the high thermal conductivity along the basal planes. On the other hand, the poor thermal properties could lead to better performance of thermoelectric materials, in which low thermal conductivity enhances the thermoelectric figure of merit (ZT) and thus the efficiency of thermoelectric energy conversion.…”
Section: Textmentioning
confidence: 99%
“…Along with the extensive studies of metal/Gr/SiO2 interfaces, the metal/Gr/metal interfaces with metal substrates like Cu, Pd and W started to get attraction in recent years [40,41]. Huang et al [42] performed the TDTR measurements on the Pd/transferred Gr/Pd interface and reported a G of 300 MWm -2 K -1 at RT for the sample with radiofrequency (rf) 6 magnetron sputtering top Pd. This value is seven times larger than that with thermal evaporation top Pd (42 MWm -2 K -1 ).…”
Section: Interface Thermal Resistance Induced By Few-layered Graphenementioning
confidence: 99%
“…Another reason may be the damage of graphene during the β-W sputtering progress, where additional channels of direct heat transport between the β-W films form and significantly enhance the thermal conductance of the interfaces. This damage enhanced phenomenon has been studied in the most recent work by Huang et al [42] In this work, they reported measurements on thermal conductance of Pd/trG/Pd interface with the top Pd prepared by either thermal evaporation or rf magnetron sputtering. The results shown that, G of the sample with the rf magnetron sputtering Pd is 300 MWm -2 K -1 at RT, seven times larger 35 than that with the thermal evaporation Pd (42 MWm -2 K -1 ).…”
mentioning
confidence: 91%